Detection of Irrigated and Non-Irrigated Soybeans Using Hyperspectral Data in Machine-Learning Models - Oliveira, Izabela Cristina de; Gava, Ricardo; Santana, Dthenifer Cordeiro; Seron, Ana Carina da Silva Cândido; Teodoro, Larissa Pereira Ribeiro; Cotrim, Mayara Favero [UNESP]; Santos, Regimar Garcia dos; Alvarez, Rita de Cássia Félix; Junior, Carlos Antonio da Silva; Baio, Fábio Henrique Rojo; Teodoro, Paulo Eduardo (MDPI, 2024)
The objectives of this work are (i) to classify soybean cultivars under different irrigation managements using hyperspectral data, looking for the best machine-learning algorithm for the classification and the input that improves the performance of the models. The experiment was implemented in the 2023/24 harvest in the experimental area of the Federal University of Mato Grosso do Sul, Câmpus Chapadão do Sul, Mato Grosso do Sul, and it was conducted in a strip scheme with seven cultivars subjected to irrigated and rainfed management. Sixty days after crop emergence, three leaves per plot were collected for evaluation by the hyperspectral sensor. The spectral data was then separated into 28 bands to reduce dimensionality. In this way, two databases were generated: one with all the spectral information provided by the sensor (WL) and one with the 28 spectral bands (SB). Each database was subjected to different machine-learning models to ascertain the improved accuracy of the models in distinguishing the different eucalyptus species. The models tested were artificial neural networks (ANN), decision trees (DT), linear regression (LR), M5P algorithm, random forest (RF), and support vector machine (SVM). The results demonstrate the effectiveness of machine-learning models in differentiating soybean management under rainfed and irrigated conditions, highlighting the advantage of hyperspectral data (WL) over selected spectral bands (SB). Models such as the support vector machine (SVM) showed the best levels of accuracy when using the entire available spectrum. On the other hand, artificial neural networks (ANN) performed well with spectral band data, demonstrating their ability to work with smaller data sets without compromising the classification.
Keywords: algorithms; computational intelligence; Glycine max; spectral bands; vegetation indices